Determinants of stock market performance in Malaysia: inflation rate, crude oil price, exchange rate, gross domestic product and money supply / Muhammad Haziq Kamarulzaman and Nurul Musfirah Zulkefli - Kamarulzaman, Muhammad Haziq; Zulkefli, Nurul Musfirah (Faculty of Business and Management, 2019)
For years, the study of determinants for stock market performance are well-documented. However, most of the studies are focus on the macroeconomic factors in the developed country context. In light of this, this research intends to bright the gap by examining the factors that affect the stock market performance in developing country namely Malaysia. More specifically, this research aims to extend the current literature reviews by including inflation rate, crude oil price, exchange rate, gross domestic product and money supply in determining their relationships with the Malaysian stock market performance. By using Ordinary Least-Square regression method in E-views 10, multiple linear regression analysis is performed to examine the hypotheses and statistical relationships in a quarterly basis from 1st Quarter 2006 to 2nd Quarter 2018. The results conclude that inflation rate, crude oil price and exchange rate have a positive and negative relationship respectively with Malaysian stock market performance. On the other hand, this research also indicates that both the gross domestic product and money supply have an insignificant relationship with Malaysian stock market performance. We hope that the result of this study could fill a gap in the field of stock market performance in developing countries.